Effect of water stress on locomotor performance in Pleurodema nebulosum (Anura: Leptodactylidae) a native frog from the Argentina Monte desert - Ontivero, Roberto Emanuel (2024)
Locomotion is a fundamental aspect in the life cycle of any organism, and plays a crucial role in survival, feeding, escaping from predators, territoriality, and reproduction. Locomotion in amphibian anurans includes swimming, walking, jumping, climbing, and gliding. Amphibians living in arid regions face a constant compromise between hydration balance and locomotor performance. We studied the effects of water stress on the locomotion of the frog Pleurodema nebulosum, a specialist from the Monte Desert. Locomotor performance was measured through different physical variables during the jump. The locomotor performance of P. nebulosum showed a significant decrease in the magnitudes associated with a decrease in body hydration. Our study demonstrated how a desert adapted frog (P. nebulosum) showed changes in locomotion related to the loss of body water. Additionally, we observed an abrupt drop in locomotion with 15% desiccation, followed by a plateau where the evaluated pa rameters remained stable. Pleuroderma nebulosum showed a clear adaptation to extreme desiccation. The frogs are rarely found in optimal hydration conditions as the environment in which they develop is extremely stressful from a water perspective. The data evaluated here are the beginning of a deeper exploration of the desert ad aptations of South American desert frogs.